2018
DOI: 10.1038/s42004-018-0009-z
|View full text |Cite
|
Sign up to set email alerts
|

Performing radiosynthesis in microvolumes to maximize molar activity of tracers for positron emission tomography

Abstract: Positron emission tomography (PET) is a molecular diagnostic imaging technology to quantitatively visualize biological processes in vivo. For many applications, including imaging of low-tissue density targets (e.g., neuroreceptors), imaging in small animals, and evaluation of novel tracers, the injected PET tracer must be produced with high molar activity to ensure low occupancy of biological targets and avoid pharmacologic effects. Additionally, high molar activity is essential for tracers with lengthy synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 52 publications
0
55
0
4
Order By: Relevance
“…As a demonstration of the ability to perform a preclinical imaging study with [ 18 F]FET produced using the microscale method, we prepared [ 18 F]FET of different molar activities to investigate the impact on in vivo imaging. It has been previously seen with imaging of [ 18 F]Fallypride that molar activity can significantly affect the PET imaging contrast in the striata of the brain (Sergeev et al 2018b), whereas variations in molar activity of [ 18 F]FDOPA were reported not to impact the imaging of neuroendocrine tumors (Kuik et al 2015).…”
Section: Microscale [ 18 F]fet Synthesis Optimization and Automationmentioning
confidence: 99%
See 1 more Smart Citation
“…As a demonstration of the ability to perform a preclinical imaging study with [ 18 F]FET produced using the microscale method, we prepared [ 18 F]FET of different molar activities to investigate the impact on in vivo imaging. It has been previously seen with imaging of [ 18 F]Fallypride that molar activity can significantly affect the PET imaging contrast in the striata of the brain (Sergeev et al 2018b), whereas variations in molar activity of [ 18 F]FDOPA were reported not to impact the imaging of neuroendocrine tumors (Kuik et al 2015).…”
Section: Microscale [ 18 F]fet Synthesis Optimization and Automationmentioning
confidence: 99%
“…Safe preparation of various target-specific PET tracers is a complex and expensive process, requiring skilled personnel operating expensive automated radiosynthesis equipment within radiation-shielded "hot cells". With conventional apparatus, in which the chemistry is carried out in mL volume scales, relatively high reagent amounts (1 s to 10s of mg) are needed to achieve a sufficient concentration for good reaction yield in a short time, and for [ 18 F]fluoride chemistry high amounts of radioactivity (10s of GBq) are needed to achieve high molar activity (Sergeev et al 2018a). These factors contribute to inefficient use of resources in the preparation of small batches of tracers, such as needed for preclinical imaging, or for a single clinical PET scan, where much of the prepared batch would be wasted.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, for microfluidic chips that do not require large supporting pumps and valves, the overall system size can be much more compact, and potentially the system can be shielded and operated on a benchtop without the need for a conventional radiochemistry hot cell. An added advantage of low reaction volume is an improvement in molar activity of the synthesized PET tracer compared to macroscale methods (Javed et al, 2014; Sergeev et al, 2018); high molar activity is critical for imaging of scarce biological targets (e.g. neuroreceptors).…”
Section: Introductionmentioning
confidence: 99%
“…: NaOH) or acid (e.g. : HCl) to form the 4-[ 18 F]uorobenzoic acid ([ 18 F]FBA) intermediate product (8,9). However, this method requires an intermediate purication step to remove the water prior to the nal coupling step.…”
Section: Concentration and Reaction Timementioning
confidence: 99%
“…[5][6][7] Our group has also successfully demonstrated the synthesis of high molar activity radiotracers using this all-electronic microuidic radiosynthesizer. 8 In this report, we further expand the applications from 2-step nucleophilic uorination of aliphatic substrates to a more challenging and complicated reaction, which involves a 3-step nucleophilic uorination of an aromatic substrate. […”
Section: Introductionmentioning
confidence: 99%